Systematic review and meta-analysis of the growth performance and carcass composition of Nile tilapia (Oreochromis niloticus) fed dietary copra meal - Magbanua, Tzodoq Obrero; Ragaza, Janice Alano (Frontiers in Sustainable Food Systems, 2022)
Nile tilapia (Oreochromis niloticus) is one of the most cultured species in the aquaculture industry. However, its market price is affected by the increasing cost of fishmeal. Plant-based proteins are being used to mitigate the problem. This paper comprehensively quantified the growth performance and carcass composition of Nile tilapia fed copra meal via systematic review and meta-analysis. The literature review and paper selection were done based on the preferred reporting items for systematic reviews and meta-analysis method. The data from peer-reviewed papers that qualified from the inclusion screening criteria such as standard error reporting, feeding period, absence of dietary supplements, tilapia development stage, and crude protein levels were subjected to meta-analysis. Results showed that growth and feed utilization parameters were significantly different (P ≤ 0.05), favoring the control over the plant-based diets. Moreover, the pooled estimate of carcass composition of fish fed copra meal-based diet was not significantly different with that of fish fed fishmeal-based diet (P > 0.05) except for ash content (P < 0.05). The feeding period, crude protein level, fish development stage, and dietary copra inclusions were subjected to meta-regression analysis due to high and statistically significant I2 values to determine the sources of heterogeneity. The residual I2 values showed that these factors did not affect the heterogeneity of the data presented for copra meal. Nonetheless, data from meta-analysis using model coefficients revealed that the minimum required levels are 594 g kg-1, 617 g kg-1, and 462 g kg-1 of dietary copra meal are needed for optimum growth performance, feed utilization, and carcass composition of Nile tilapia, respectively. The study showed that systematic review and meta-analysis can be a useful tool in optimizing plant-based diets for aquaculture species.